Spreadsheets in chemical engineering education: a tool in process design and process integration - Ferreira, Eugénio C. (2004)
Recent developments in embedding numerical optimization procedures with linear and nonlinear solvers within a spreadsheet environment have greatly enhanced the use of these tools for teaching chemical process design and process integration. Student skills with respect to these topics are usually gained by complex and expensive modular simulators, e.g. ASPEN Plus® or algebraic tools such as GAMS® or AMPL®. However, modular simulators have a significant learning curve, and algebraic modeling languages are usually ignored once students commence careers. This paper demonstrates how the Solver feature of the Excel® spreadsheet is used for the optimization of several chemical engineering systems, including pollution prevention problems and mass-exchange networks. Three nonlinear problems are examined: the (a) recovery of benzene from a gaseous emission; (b) design of a chemical reactor network; and (c) solution of material balances in the production of vinyl chloride from ethylene. Dephenolization of aqueous wastes is presented as a linear case. The ease with which these and similar process problems can be formulated and solved within the Excel® environment constitutes a major step towards teaching practical optimization and design concepts for university students.